2013
DOI: 10.1021/ie401543n
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Thermal Performance in a Two-Phase Closed Thermosiphon Using Graphene/Water Nanofluid

Abstract: In the present study, the effect of graphene/water nanofluid on the thermal performance of a two-phase closed thermosiphon (TPCT) has been considered. For the synthesis of the mentioned nanofluids, graphene with a thickness of 4–20 nm and length of 5–10 μm has been employed. Due to the natural instability of graphene in polar solvents such as water, gum arabic (GA) has been utilized as a surfactant. Then, various nanofluids at weight concentrations of 0.02–1% were prepared and thermal properties were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 36 publications
(60 reference statements)
0
29
0
Order By: Relevance
“…In similar study, the thermal conductivity and heat transfer enhancements of MWCNTs-based water nanofluids were investigated and a noticeable enhancement was reported that was attributed to the thinning of the thermal boundary layer by MWCNTs and reducing the thermal resistance [28,29]. However, among various carbon-based nanostructures, graphene-family nano-materials (GFN) appears to over more potential due to their attractive thermal, electrical and mechanical properties [6,30,31]. In fact, GFN has found many applications including its use as high-performance coolant.…”
Section: Introductionmentioning
confidence: 99%
“…In similar study, the thermal conductivity and heat transfer enhancements of MWCNTs-based water nanofluids were investigated and a noticeable enhancement was reported that was attributed to the thinning of the thermal boundary layer by MWCNTs and reducing the thermal resistance [28,29]. However, among various carbon-based nanostructures, graphene-family nano-materials (GFN) appears to over more potential due to their attractive thermal, electrical and mechanical properties [6,30,31]. In fact, GFN has found many applications including its use as high-performance coolant.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, experiments were performed at five input powers (30,45, 60, 90 and 120 W) and the volume flow rate was 250 mL min −1 . In order to evaluate the effects of the oxidation stage and power of acids, five CNT/water nanofluids oxidized with different acids were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Azizi et al [30] investigated the effect of graphene/ water nanofluids on the thermal efficiency and resistance of two-phase closed thermosyphon (TPCT). They concluded that as the concentration increased, the thermal efficiency of the TPCT also increased.…”
Section: List Of Symbolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Azizi et al [3] analyzed experimentally the effect of graphene/water nanofluid on the thermal performance of a two-phase closed thermosyphon with various weight concentrations ranged from 0.02% to 1% at the input power of 30-150 W. The reported results showed that the highest thermal efficiency (90.2%) was obtained in the concentration of 1 wt.% and with input power of 120 W. Kim and Bang [4] carried out experiments to observe the effect of GO (graphene oxide)/water nanofluids (0.01 and 0.03 vol.%) on the heat pipe performance and capillary limits. A 25% reduction of the thermal resistance at the evaporator section was observed.…”
Section: David Publishingmentioning
confidence: 99%